Application of Steel-Concrete Composite Columns in Building Construction - Kiriparan, B.; Fernando, W.J.B.S.; Bhathiya, W.; Mendis, P.; De Alwis, A.D.; Dilina, H. (The Institution of Engineers, Sri Lanka, 2018)
Abstract: The steel concrete composites namely concrete filled steel tubular columns (CFST) and encased steel reinforced concrete (SRC) columns are becoming increasingly popular in the building industry due to the features like high strength, stiffness, fire resistance and constructability. Steel jacketing is a useful technique available for the strengthening of existing reinforced concrete columns to withstand additional loads applied from alteration such as addition of stories in existing buildings. Recent revolution in the design and application of these steel-concrete composites provides numerous advantages such like reduction in the sizes of vertical element, facilitate columns with higher slenderness, enhancing capacity of existing columns to meet the increased demands, minimize the cost involved for the fire protection and increase the construction speed. The application of design methods available in the codes, detailing of connections and construction techniques are some of the vital challenges for the designers as well as the contractors. This paper intended summarize the basic aspects to be considered in the design of a CFST column, design provisions given in EN 1994-1-1:2004, its practical application, detailing of composite columns and their connections and constructability aspects. Further, the design and construction methods of steel jacketing technique for the strengthening of existing columns will be discussed. The case studies selected from the projects involved by the Authors will be included to demonstrate applications of for CFST and steel jacketing in the building construction. Finally, based on the literature review conducted recommendation is made for further studies in areas requires lack of reference in the design and application of CFST.
Keywords: Steel-Concrete composites; composite column design; CFST Connections; Steel jacketing